PENGARUH PENGGUNAAN MULTIMEDIA INTERAKTIF TERHADAP HASIL BELAJAR DAN BERPIKIR KREATIF SISWA PADA KONSEP SISTEM PERTAHANAN TUBUH MANUSIA - Sihole, Renata (2013)
The title of research is The Effect of Using Interactive Multimedia to Learning Outcomes Students and Creative Thinking in Human System of Immunity. The purpose of this study is to analyze the effect of using interactive multimedia to learning outcomes students and creative thinking. The research method was used Quasy Experiment with research design named "Non-equivalent Control Groups Design". The instrumens used are multiple choice questions for learning outcomes test, problem description for test of creative thinking, assignment to make a poster, student questionnaire responses and interview with the teacher about lesson activity by using interactive multimedia. The research was done in class XI IPA 1 and XI IPA 2 senior high school in Bandung. The experiment class used flash and control class used slide power point as their lesson media. The result of this research shows that learning outcomes in experiment class and control class is significant different (α= 0,05) with average of N-Gain in experiment class is 0,44 and control class is 0,52. Creative thinking in experiment class and control class is not significant different, the average of N-Gain in experiment class is 0,23 and in control class is 0,24. Most of poster that made by students are good, most of the students agree that interactive multimedia makes the lesson activity more fun and can improve their comprehend about the concept. Key Word: Interactive multimedia, learning outcomes, creative thinking, the human system of immunity